A coordinated design of PSSs and UPFC-based stabilizer using Genetic Algorithm - Hassan, L.H.; Moghavvemi, M.; Almurib, H.A.F.; Muttaqi, K.M. (2013)
This paper details a new coordinated design between Power System Stabilizers (PSSs) and Unified Power Flow Controller (UPFC) using Genetic Algorithm (GA). The GA determines the optimal location for the UPFC while tuning its control parameters, resulting in the optimization of the quantity, parameters and locations of PSSs under different operating conditions. The problem is formulated as a multiobjective optimization problem in order to maximize the damping ratio(s) of the electromechanical modes, matching different numbers of PSSs with UPFC. The approach is successfully tested on the New England-New York interconnected system (16-machine and 68-bus), proving its effectiveness in damping local and inter-area modes of oscillations.